A parameter map of synthetic jet regimes based on the Reynolds and Stokes numbers: Commentary on the article by Rimasauskiene et al. (February 2016) - Broučková, Z.; Šafařík, P.; Trávníček, Z.
Abstract: Recently, Rimasauskiene et al. ([1] Mech. Syst. Signal Process. (2015) 50–51) presented an experimental study focusing on synthetic jets. Their paper presented a parameter map based on the Reynolds number. However, the map was shown without an adequate explanation, without definition of the horizontal axis, and without cross-connections with previous literature. This commentary attempts (A) to elucidate the unnecessary misunderstanding for readers and (B) to reveal that the parameter map, based on the Reynolds and Stokes numbers, can be a useful tool in the study of synthetic jets. Graphical abstract: Highlights: Commentary on incomplete article by Rimasauskiene et al. (Mech. Syst. Signal Proc.) Explanations, definitions and cross-connections with previous literature are completed. Synthetic jet existence criteria from previous literature are collected and completed. Misunderstanding for readers of the article by Rimasauskiene et al. is rectified. Reasonability of the Reynolds–Stokes numbers map for synthetic jets is suggested.